Anti-Tuberculosis Coumarinolignans from Daphne mucronata - Ferheen, Sadia; Rehman, Aziz-ur; Azam Rasool, Muhammad; Naqvi, Beena; Imran, Muhammad; Ali Khan, Rashid; Ali Kalhoro, Mahboob; Malik, Abdul (Asian Journal of Chemistry, 2014)
Two new linearly fused coumarinolignans named mucronin-A (1) and mucronin-B (2) have been isolated from the whole plant of Daphne mucronata along with two other known compounds i.e., umbelliferone (3) and coumarin (4). The structures of the isolated compounds 1-4 were elucidated by chemical and spectroscopic methods including 1D-NMR, 2D-NMR and HR-FAB-MS. Both of the new isolated compounds 1 and 2 showed significant antituberculosis activity.